HUBUNGAN TINGKAT STRES DENGAN PENURUNAN SISTEM IMUN PADA MAHASISWA TINGKAT IIA AKADEMI KEPERAWATAN PANTI KOSALA SURAKARTA - Ditya Yankusuma Setiani; Anisa Heni Purwanti; Nia Asmarani (KOSALA : Jurnal Ilmu Kesehatan, 2015)
ABSTRACTIntroduction: This study was stress is the body’s response is not specific to any load and demands. Based on observations in the Academy of Nursing Panti Kosala Surakarta especially in level IIA, the authors conducted research at random to ask direct. Most of them complained of stress and dizziness since the coursework overload and besides asking also carried out objectively the data retrieval with observations. From observations made, there are approximately 10 students from 43 students experiencing symptoms such as anxious, tense and not accept lessons concentration and 4 of them have often complained of pain during a lecture.The purpose of the research: Was to find out the relationship stress levels with decreased immune system on student level IIA Academy of Nursing Panti Kosala Surakarta.The Subject of research: Is the entire student level IIA Academy of Nursing Panti Kosala Surakarta amounted to 43 people. The technique used is the saturated samples. Saturated samples is a way of sampling by taking all members of the population to be sampled.The result of the research: Was the number of respondents who experienced mild stress levels of 23 respondents (53,5%) and respondents who experienced a decline in the immune system when it is being stressed that by 30 respondents (69,8%). From the Chi Square test results with the program SPSS version 18.0 with α = 5% (0,05) acquired p of 0,024. The value of less than 0,05 Ha accepted meaning and Ho is rejected.Conclusion of the research: Was the existence of relationship stress levels with decreased immune system on student level IIA Academy of Nursing Panti Kosala Surakarta.Keywords: Stress Levels, Decreased Immune System